2017
DOI: 10.1155/2017/4815251
|View full text |Cite
|
Sign up to set email alerts
|

Tunable SnO2 Nanoribbon by Electric Fields and Hydrogen Passivation

Abstract: Under external transverse electronic fields and hydrogen passivation, the electronic structure and band gap of tin dioxide nanoribbons (SnO2NRs) with both zigzag and armchair shaped edges are studied by using the first-principles projector augmented wave (PAW) potential with the density function theory (DFT) framework. The results showed that the electronic structures of zigzag and armchair edge SnO2NRs exhibit an indirect semiconducting nature and the band gaps demonstrate a remarkable reduction with the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Table 1 shows the band gap energies of SnO2 NPs (3.50 eV) and Zndoped SnO2 NPs (1% and 5%) (3.42 eV and 3.34 eV). These band gap energies of theses NPs exhibited direct electronic transitions [46]. UV results showed that the Zn doping effects on the optical properties of SnO2 NPs due to the presence of stacking faults.…”
Section: Uv-vis Analysismentioning
confidence: 89%
“…Table 1 shows the band gap energies of SnO2 NPs (3.50 eV) and Zndoped SnO2 NPs (1% and 5%) (3.42 eV and 3.34 eV). These band gap energies of theses NPs exhibited direct electronic transitions [46]. UV results showed that the Zn doping effects on the optical properties of SnO2 NPs due to the presence of stacking faults.…”
Section: Uv-vis Analysismentioning
confidence: 89%